Simulasi Pola Aliran Dan Pola Sedimentasi Pada Danau Cipogas Kecamatan Rambah Kabupaten Rokan Hulu - Fahrul Rozi; Mudjiatko Mudjiatko; Rinaldi Rinaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Cipogas lake has a non-uniform topography, that non-uniform topography caused flow patterns. Which results in a non-uniform of velocity and sediment distribution and then influences the changing trend of the reservoir bed configuration. Hydraulic simulation has used a RMA-2 model to determine flow patterns and velocity distribution. Topographic data, flood discharge, and surface water elevation are used as basic data for RMA-2 processing. Sediment transport simulation has used a SED2D module to generate sediment movements. The grain size and sediment concentration are used as a basis for SED2D processing. The simulation results showed that the flow pattern affects the velocity distribution and sediment distribution at certain times in the lake so that there is a change in the lake bed configuration. The bed configuration of the cipogas lake based on simulation results is classified in the Transition and Dunes. Keyword: flow patterns, sediment distribution, bed configurations